ANALISIS PENENTUAN DAN KEBIJAKAN STRATEGI PENGEMBANGAN SEKTOR BASIS WILAYAH KABUPATEN PESISIR BARAT - Rizaldy, Muhammad Fahmi; Asnani, Asnani (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2024)
National development has the aim of making society more prosperous by improving the community's economy. Regional development must be based on a strong economic sector, in accordance with regional resources and involving various parties. One of the problems that often arises in policy planning and regional development direction is that regulations and policies regarding regional planning are not based on local potential and natural resources. The research conducted in Pesisir Barat Regency with the purpose of determining the sector base and analyzing the performance of economic sectors as consideration for development strategies in this district. This study using Location Quotient (LQ) and Shift Share (SS) analysis tools. There are eight sectors that are the basis with the top three LQ values in a row, there are the Agriculture, Forestry and Fisheries Sector, Government Administration Sector, Defenses and Securities Mandatory Social, and Real Estate Sector. From the results of the SS analysis, there were five sectors that showed positive performance from 2020 to 2021. The positive results obtained in the sectors that became the basis of the sector were education services as well as the health sector and social activities. Development planning in Pesisir Barat Regency can be in the form of Development of Maritime Agroecotourism Area Models.